Critical analysis of doctrinal approaches to the definition of “biological terrorism” - О. V. Shamsutdinov (Bulletin of Kharkiv National University of Internal Affairs)
With the purpose of formulating a universal definition of the “biological terrorism” concept, the author clarifies the content and features of the generic concept of “terrorism”. In particular, the author examines the definitions of terrorism and its main features available in the scientific literature, as well as the approaches to the interpretation of its content used in national legislative and international legal acts. It has been argued that terrorism is not only criminal behaviour, but also a certain ideology which justifies the purpose of terrorist activity and the mechanisms for achieving it. On this basis, two doctrinal approaches to understanding terrorism, such as comprehensive and applied, have been identified. The article illustrates the use of the method of defining terrorism in international law by criminalising certain of its socially dangerous manifestations using specific examples. The main criminal features of terrorism have been identified. Terrorism has been defined as socially dangerous criminal acts provided for by international and national law, which consist of demonstrative public violence in a generally dangerous manner or with particular cruelty, as well as threats, organisation, preparation, logistical, financial and other support or incitement to commit such acts aimed at intimidating the population, inducing specific institutions or individuals to commit or refuse to commit certain acts, or with the aim of destabilising or destroying law and order.